Cannabidiol improves Nile tilapia cichlid fish welfare - Camargo-dos-Santos, Bruno [UNESP]; Bellot, Marina Sanson [UNESP]; Guermandi, Isabela Inforzato [UNESP]; Favero-Neto, João [UNESP]; da Silva Rodrigues, Maira [UNESP]; da Costa, Daniel Fernandes [UNESP]; Nóbrega, Rafael Henrique [UNESP]; Filev, Renato; Gonçalves-de-Freitas, Eliane [UNESP]; Giaquinto, Percília Cardoso [UNESP] (Springer Nature, 2022)
Cannabidiol (CBD) is a substance derived from Cannabis sativa, widely studied in medicine for controlling neural diseases in humans. Besides the positive effects on humans, it also presents anxiolytic proprieties and decreases aggressiveness and stress in mammals. Therefore, CBD has the potential to increase welfare in reared animals, as it seems to reduce negative states commonly experienced in artificial environments. Here, we tested the effect of different CBD doses (0, 1, 10 and 20 mg/kg) on aggressiveness, stress and reproductive development of the Nile tilapia (Oreochromis niloticus) a fish reared worldwide for farming and research purposes. CBD mixed with fish food was offered to isolated fish for 5 weeks. The 10 mg/kg dose decreased fish’s aggressiveness over time, whereas 20 mg/kg attenuated non-social stress. Both doses decreased the baseline cortisol level of fish and increased the gonadosomatic index. However, CBD 1 and 10 mg/kg doses decreased the spermatozoa number. No CBD dose affected feeding ingestion and growth variables, showing that it is not harmful to meat production amount. Despite the effect on spermatozoa, CBD supplementation exhibits high potential to benefit animals’ lives in artificial environments. Therefore, we showed for the first time that CBD could be used as a tool to increase non-mammal welfare, presenting a great potential to be explored in other husbandry and captivity species.